The role of pedagogical management in the blended learning system of higher education in the Russian Federation - Chernova, Natalia (2021)
This research contributes to the study of pedagogical management in the blended learning system, which has become especially widespread within the context of the Covid-19 pandemic. Pedagogical management is the process of managing the pedagogical process, which creates conditions for students to acquire knowledge, skills and abilities in accordance with their qualifications. The article deals with the essence of pedagogical management in the context of teaching students of higher education institutions.